DAMPAK TINGKAT PENDIDIKAN IBU TERHADAP PRESTASI BELAJAR SISWA KELAS IV SDN 004 SEI JALAU KECAMATAN KAMPAR UTARA - Khairun Nisa; Febrina Dafit (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to describe the impact of maternal education level on the learning achievement of Class IV students at SDN 004 Sei Jalau, North Kampar District. The research method used is a descriptive quantitative method. The population and sample of this research were 34 respondents. Data collection techniques and instruments include interviews, questionnaires, observation and documentation. Data analysis is carried out through data review. From the results of the research carried out, the result is that the mother's education level can have an influence on the learning achievement of class IV students at SDN 004 Sei Jalau, North Kampar District. Students have a higher level of achievement because they have mothers who have a fairly high level of education who provide attention and participate in helping children learn. Likewise, mothers who have a low level of education can usually only motivate their children to be active in school and study so they can achieve high levels of achievement.